Pelatihan Aplikasi Program Eviews Bagi Mahasiswa Dan Dosen Fakultas Ekonomi Dan Bisnis Universitas Sam Ratulangi : Capacity Building through EViews Application Training for Students and Lecturers of the Faculty of Economics and Business, Sam Ratulangi University - Rotinsulu, Tri Oldy; Rorong, Ita Pingkan F; Sari, Greydi Normala (Vivabio: Jurnal Pengabdian Multidisiplin, 2025)
The training program on data processing using the EViews software for lecturers and students aims to address the limited understanding and skills in managing and analyzing statistical and econometric data in a digital environment. In the current era of digital transformation, many lecturers and students have not yet fully mastered the use of analytical software such as EViews for conducting more complex data analyses, both in academic research and in teaching activities. This limitation results in the suboptimal utilization of EViews for statistical analysis, regression techniques, and time-series data processing, all of which constitute essential components of studies in economics and business. ABSTRAK Pelatihan pengolahan data menggunakan aplikasi EViews bagi dosen dan mahasiswa bertujuan untuk mengatasi keterbatasan pemahaman serta keterampilan dalam mengelola dan menganalisis data statistik dan ekonometrika secara digital. Di era transformasi digital saat ini, masih banyak dosen dan mahasiswa yang belum menguasai penggunaan perangkat lunak EViews untuk analisis data yang lebih kompleks, baik dalam konteks penelitian akademik maupun proses pembelajaran. Kondisi tersebut menyebabkan pemanfaatan EViews dalam analisis statistik, regresi, maupun data time series belum optimal, padahal kemampuan tersebut sangat penting dalam studi ekonomi dan bisnis. Pelatihan ini dirancang agar mahasiswa mampu memahami dasar-dasar penggunaan EViews, meliputi pengolahan data, analisis deskriptif, regresi sederhana dan berganda, pengujian asumsi klasik, serta visualisasi data. Sementara itu, bagi dosen, pelatihan difokuskan pada penguasaan teknik analisis lanjutan seperti model time series dan panel data sehingga dapat diterapkan dalam penelitian maupun pengajaran. Target khusus kegiatan ini adalah meningkatkan keterampilan teknis peserta dalam menggunakan EViews, mempersiapkan mereka untuk memanfaatkan teknologi digital secara efektif dalam analisis data, serta mengoptimalkan penggunaan EViews pada berbagai aktivitas akademik berbasis data besar. Luaran kegiatan PKM_K2 ini berupa satu artikel ilmiah yang akan dipublikasikan pada jurnal pengabdian multidisiplin VIVABIO UNSRAT serta disebarluaskan melalui media online dan video YouTube.                  This training is designed to equip students with foundational competencies in EViews, including data processing, descriptive analysis, simple and multiple regression, classical assumption testing, and data visualization. For lecturers, the program focuses on advanced analytical techniques such as time-series models and panel data analysis to support their research and teaching responsibilities.                  The specific objectives of this program are to enhance participants’ technical proficiency in using EViews, prepare lecturers and students to effectively employ digital tools in data analysis, and optimize the integration of EViews into academic and research activities involving large datasets. The expected output of the PKM_K2 initiative includes a scientific article to be published in the multidisciplinary service journal VIVABIO UNSRAT, as well as dissemination through online media and a YouTube video. Keywords: capacity development, technical skills, digital innovation, learning enhancement